2017
DOI: 10.3892/ol.2017.7495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harmaline on cell growth of human liver cancer through the p53/p21 and Fas/FasL signaling pathways

Abstract: Abstract. The effects of harmaline on the viability and apoptosis of human liver carcinoma were investigated in vitro. HepG2 cells were treated with harmaline (0-10 µM), and the proliferation and apoptosis of HepG2 cells were investigated using an MTT assay and flow cytometry, respectively. The protein expression of cellular tumor antigen p53 (p53), cyclin-dependent kinase inhibitor 1 (p21), tumor necrosis factor receptor superfamily member 6 (Fas), Fas ligand (FasL) and caspase-8 was subsequently measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The results presented here suggested that harmaline obstructs the growth of cancerous cells and resonates well with earlier studies from other groups. 63 , 64 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here suggested that harmaline obstructs the growth of cancerous cells and resonates well with earlier studies from other groups. 63 , 64 …”
Section: Resultsmentioning
confidence: 99%
“… 62 Harmaline exhibits potential anticancer activity in multiple cancer cell lines with a low risk of toxic side effects, as reported by previous studies. 63 , 64 All of these studies direct that harmaline possesses the potential for using it as a novel antioxidant and antitumor agent in anticancer therapy. 57 …”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level SAHA treatment caused signi cant changes in proteins involved in both cell cycle and cell phenotype. p53 is plays an important role in many molecular processes including DNA transcription and repair, cell cycle, genomic stability, chromosome segregation, apoptosis, and angiogenesis [50]. p21 is a potent cyclin-dependent kinase inhibitor that can stabilize the interaction between cyclin-dependent kinase (CDK)-4/6 and cyclin D and promote the formation of cyclin D/CDK complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increase of p21 has also been demonstrated to be induced by a variety of environmental genotoxic agents (including chemicals and toxins) . The cytotoxicity assay using human hepatocellular (HepG2) cells revealed that harmaline can activate the Fas/FasL signaling pathway to inhibit the cell viability and induce the apoptosis of HepG2 by increasing the expression of p53 , p21, caspase‐3, and caspase‐8 . Aflatoxin B1 can also induce the senescence and apoptosis of germ cells in mouse testis through the upregulation of p53 and p21 .…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The cytotoxicity assay using human hepatocellular (HepG2) cells revealed that harmaline can activate the Fas/FasL signaling pathway to inhibit the cell viability and induce the apoptosis of HepG2 by increasing the expression of p53, p21, caspase-3, and caspase-8. 49 Aflatoxin B1 can also induce the senescence and apoptosis of germ cells in mouse testis through the upregulation of p53 and p21. 50 These results show that p21, as a downstream factor, can give rise to the downregulation of the cell cycle.…”
Section: Effect Of Pft-α On the Expression Of Apoptosisrelated Protmentioning
confidence: 99%